2002
DOI: 10.1203/00006450-200202000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Partial Liquid Ventilation Reduces Release of Leukotriene B4 and Interleukin-6 in Bronchoalveolar Lavage in Surfactant-Depleted Newborn Pigs

Abstract: Perfluorocarbons have been shown to reduce the inflammatory process generated by alveolar macrophages in vitro. The aim of this study was to evaluate the impact of different ventilator modalities such as partial liquid ventilation (PLV), conventional ventilation (CV), and high-frequency oscillatory ventilation (HFOV) on the release of inflammatory mediators in vivo. Acute lung injury was induced in 30 male piglets by repeated saline lavage (arterial oxygen tension, Ͻ60 mm Hg; fraction of inspired oxygen, 1.0).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…By contrast, the effect of PLV with a PFC on TNF-α levels did not follow a consistent trend in the various animal studies [71,83,[88][89][90][91] and may depend on where TNF-α levels were assessed. For example, Kawamae and coworkers investigated the effect of PLV on TNF-α levels in an hydrochloric acid-induced rat lung-injury model [91].…”
Section: Review Lehmlermentioning
confidence: 87%
See 1 more Smart Citation
“…By contrast, the effect of PLV with a PFC on TNF-α levels did not follow a consistent trend in the various animal studies [71,83,[88][89][90][91] and may depend on where TNF-α levels were assessed. For example, Kawamae and coworkers investigated the effect of PLV on TNF-α levels in an hydrochloric acid-induced rat lung-injury model [91].…”
Section: Review Lehmlermentioning
confidence: 87%
“…By contrast, studies in different lung-injury models generally showed a decrease in expression of several cytokines, such as IL-1β [23,25,27], IL-6 [27,71,73,74] and IL-8 [23,27,28,73,[85][86][87], in the PLVtreatment group compared with the respective GV-treatment group. By contrast, the effect of PLV with a PFC on TNF-α levels did not follow a consistent trend in the various animal studies [71,83,[88][89][90][91] and may depend on where TNF-α levels were assessed.…”
Section: Review Lehmlermentioning
confidence: 98%
“…The pulmonary conditions were not completely the same as with neonatal patients. Since fixed ventilatory settings, high FIO 2 , different PEEP and inspiratory time, and deep anesthesia are commonly used in animal studies with MAS (7,12,16,28,29), some atelectasis before lung injury would be expected. Therefore, the preinjury alveolar-arterial oxygen difference might be worse than for a normal infant breathing spontaneously with room air (10,17,18,28).…”
Section: Discussionmentioning
confidence: 99%
“…15 In preterm pigs, conventional tidal volume ventilation induced greater increases in leukotriene-B 4 and IL-6 than high-frequency oscillatory ventilation or partial liquid ventilation; however, BAL levels of TNF-α were not different among the groups. 28 Altemeier and colleagues 29 pretreated rabbits with endotoxin before mechanical ventilation with a tidal volume of 15 mL/kg without PEEP for 8 h and found that endotoxin combined with mechanical ventilation resulted in significant increases in BAL levels of TNF-α, IL-8, growth-related oncogene-α, and MIP-1. Endotoxin or mechanical ventilation alone did not increase these cytokines.…”
Section: Cytokines and Chemokines In Experimental Studiesmentioning
confidence: 99%